2022
DOI: 10.1002/ijc.34050
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation testing with S5 for triage of high‐risk HPV positive women

Abstract: Methylation of host and viral genes is promising for triage of women with high‐risk human papillomavirus infections (hrHPV). Using a population‐based sample of hrHPV positive women with cervical biopsies within 12 months after cervical screening, the clinical value of the S5 methylation classifier (S5), HPV genotyping and cytology were compared as potential triage tests, for outcomes of cervical intraepithelial neoplasia (CIN) grade 3 or greater (CIN3+), CIN2+ and CIN2, and the area under the curve (AUC) calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 56 publications
1
13
0
Order By: Relevance
“…Elevation of S5 DNA methylation correlates directly with increasing severity of disease and inversely with lead time to diagnosis (Figure 2). S5 methylation testing has 92.8% (95CI: 85.7–97.0) sensitivity for detecting prevalent CIN3 and 100% sensitivity (95%CI: 66.4–100) for detecting prevalent ICC (based on 97 women with CIN3 and 9 with ICC), which is consistent with earlier reports of S5 methylation performance 15,18–20,30,31 . The accumulating results thus indicate that as a triage test, S5 would miss a few prevalent CIN3s and almost no invasive cancers.…”
Section: Discussionsupporting
confidence: 86%
“…Elevation of S5 DNA methylation correlates directly with increasing severity of disease and inversely with lead time to diagnosis (Figure 2). S5 methylation testing has 92.8% (95CI: 85.7–97.0) sensitivity for detecting prevalent CIN3 and 100% sensitivity (95%CI: 66.4–100) for detecting prevalent ICC (based on 97 women with CIN3 and 9 with ICC), which is consistent with earlier reports of S5 methylation performance 15,18–20,30,31 . The accumulating results thus indicate that as a triage test, S5 would miss a few prevalent CIN3s and almost no invasive cancers.…”
Section: Discussionsupporting
confidence: 86%
“…The S5 has been substantially evaluated as a triage test for hrHPV‐positive nonvaccinated women and has demonstrated improved triage performance compared to hrHPV genotyping or cytology alone or combined. 40 , 41 , 42 , 43 These observations suggest that the S5 classifier could help identify women with a high short‐term risk of progression to cancer who need immediate treatment. Hernandez et al 41 suggested that the S5 classifier could reduce colposcopy referrals by 30% to 50% without affecting sensitivity for CIN2+ and CIN3+, therefore significantly improving cost‐effectiveness to allow identification of women with a true risk of cancer.…”
Section: Methylation Of Combined Host and Hpv Gene...mentioning
confidence: 98%
“…In addition, S5 had the ability to distinguish between <CIN2, CIN2 and CIN3+, a finding of importance for managing CIN2, given the complexity and uncertainty associated with this diagnosis. 43 …”
Section: Methylation Of Combined Host and Hpv Gene...mentioning
confidence: 99%
“…This assay has shown promise for the detection of CIN2+ and CIN3+ in many studies conducted in several different countries. [164][165][166][167][168][169] Other Assays As an expression of E6 and E7 oncoproteins is much higher in cervical precancers compared with transient infections, there has been interest in measuring these proteins to detect transforming HPV infections. Specifically, a lateral flow assay was developed to target the HPV E6 oncoprotein from HPV types 16 and 18 (OncoE6; Arbor Vita Corporation) that may have triage applications in low-resource settings.…”
Section: Hpv Genotypingmentioning
confidence: 99%
“…Several studies have also evaluated a triage classifier assay (“S5 classifier”) based on DNA methylation of the late regions of HPV16, HPV18, HPV31, and HPV33 combined with the promoter region of a human gene EPB41L3. This assay has shown promise for the detection of CIN2+ and CIN3+ in many studies conducted in several different countries 164–169 …”
Section: Introductionmentioning
confidence: 99%